A 290-359 GHz Push-Push Signal Source with 1.7 dBm Pmax using Variable Inductance in SiGe BiCMOS Technology - Breun, Sascha; Schrotz, Albert-Marcel; Koch, Manuel; Issakov, Vadim; Weigel, Robert (2024 IEEE Wireless and Microwave Technology Conference, WAMICON 2024, 2024)
This paper presents a fully integrated, continuously tunable 290-359 GHz high output power signal source achieving 1.7dBm peak output power (Pmax) at 320 GHz. A continuous frequency tuning range of 69 GHz (21.3 %) is achieved by tuning both, the capacitance and effective inductance of a push-push Colpitts voltage-controlled oscillator (VCO) at around 160 GHz and subsequent frequency multiplication by a factor of 2. A phase noise of -74 dBc/Hz/-98 dBc/Hz at 1MHz/10MHz offset from the carrier, as well as a power variation below 5.6 dB is achieved. The prototype is fabricated using an advanced 90nm SiGe BiCMOS technology with target ft/fmax of 300GHz/500GHz and consumes around 457mW. This corresponds to a DC-to-RF efficiency of 0.33% and FoMT of -170 dBc/Hz, which is very competitive among fully integrated signal sources, considering the high output power and tuning range.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Colpitts oscillator; frequency doubler; push-push oscillator; radar; voltage-controlled oscillator (VCO)